A Hybrid Halide Perovskite Birefringent Crystal. (30th March 2022) - Huang, Weiqi; Zhang, Xu; Li, Yanqiang; Zhou, Yang; Chen, Xin; Li, Xiaoqi; Wu, Fafa; Hong, Maochun; Luo, Junhua; Zhao, Sangen
Abstract: Birefringent crystals that can modulate the polarization of light play a significant role in modern optical devices including polarizing microscopes, optical isolators, and achromatic quarter‐wave plates. To date, commercial birefringent crystals are exclusively limited to purely inorganic compounds. Here we report a new organic–inorganic hybrid halide, MLAPbBr4 (MLA=melamine), which features a (110)‐oriented layered perovskite structure. Although the 6s 2 lone‐pair electrons of Pb 2+ cations are stereochemically inert, MLAPbBr4 exhibits a birefringence of 0.322@550 nm, which exceeds those of all commercial birefringent crystals. The first‐principles calculations reveal that this birefringence should be ascribed to the highly dislocated π‐conjugation of MLA cations and high distortion of PbBr6 octahedra. This work highlights the persistently neglected great potential of hybrid halide perovskites as birefringent crystals. Abstract : MLAPbBr4 (MLA=melamine) features a layered perovskite structure consisting of highly distorted PbBr6 octahedra and planar MLA + cations. As a result, it exhibits large birefringence up to 0.322@550 nm. This birefringence makes MLAPbBr4 capable of easily dividing incident light into two polarized rays (e‐ray and o‐ray).